2022
DOI: 10.1111/ajt.16834
|View full text |Cite
|
Sign up to set email alerts
|

Association of donor hepatitis C virus infection status and risk of BK polyomavirus viremia after kidney transplantation

Abstract: Kidney transplantation (KT) from deceased donors with hepatitis C virus (HCV) into HCV‐negative recipients has become more common. However, the risk of complications such as BK polyomavirus (BKPyV) remains unknown. We assembled a retrospective cohort at four centers. We matched recipients of HCV‐viremic kidneys to highly similar recipients of HCV‐aviremic kidneys on established risk factors for BKPyV. To limit bias, matches were within the same center. The primary outcome was BKPyV viremia ≥1000 copies/ml or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“….03) 43 . The author suggested that kidney transplant recipients from In conclusion, HCV-negative kidney transplant recipients who receive organs from HCV-viremic donors do not appear to be at increased risk for post-transplant viral complications when DAAs therapy is started within the first month after transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“….03) 43 . The author suggested that kidney transplant recipients from In conclusion, HCV-negative kidney transplant recipients who receive organs from HCV-viremic donors do not appear to be at increased risk for post-transplant viral complications when DAAs therapy is started within the first month after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier report by Molnar et al., evaluating the risk of BK viremia in HCV‐negative kidney transplant recipients of HCV NAT+ kidneys, the group found no difference in the primary outcome of incidence of any BK viremia between the groups. However, in their experience, kidney transplantation from HCV NAT+ donors was associated with an increased risk for BK viremia ≥10 000 copies/ml (HR = 1.69, p = .03) 43 . The author suggested that kidney transplant recipients from HCV NAT+ donors might have more difficulty in clearing BK viremia once developed.…”
Section: Discussionmentioning
confidence: 99%
“…did not prove the association between donor-derived HCV viremia and CMV viremia, whereas the more recent study by Molnar et al. found that KTRs undergoing HCV NAT D+/R- transplant may be at increased risk of developing high-level BK viremia [ 65 , 66 ]. In the THINKER and EXPANDER studies, no serious complications were observed in the early posttransplant period [ 26 , 41 , 42 ].…”
Section: Optimal Timing Of Daa Initiationmentioning
confidence: 99%
“…Concerns have also been raised regarding the increased risk of the development of BK viraemia and cytomegalovirus (CMV) and severe cases have coincided with the formation of de novo donor specific antibodies ( 32 , 36 ). Studies to date have not noted significant difference in the prevalence of such viral complications, but when such events occur, the severity has been increased ( 36 , 37 ). Consequently, thorough surveillance strategies will be required.…”
Section: Future Considerations For United Kingdom Applicationmentioning
confidence: 99%